The Myongji University Library Experience: The Impact of the ERASMUS+ Personnel Exchange Program on the Professional Development of University Librarians - Tufanyazıcı, Ece; Bilek, Fatma (Information World, 2023)
University libraries are units that support education, training within the scope of research and development activities of universities. University libraries provide users with lifelong learning skills in the production, access and management of ever-increasing knowledge while providing access to current, reliable and universal knowledge to serve society. Librarians working in university libraries need to continue their professional development in order to meet the increasing information needs of users, to be aware of the changes in user expectations, to follow current developments and to provide better service to users. In this context, librarians, as university personnel, support their professional development by participating in various in-service training activities such as workshops, courses, seminars, and conferences both domestically and internationally. The ERASMUS+ Personnel Exchange Program is one of the activities for that enable university staff and librarians to acquire new experiences and competencies abroad. In this study, the impact of the ERASMUS+ Personnel Exchange Program on the professional development of librarians working in university libraries, how it affects the perspectives of librarians participating in the mobility, and the experiences gained in the Myongji University Library in South Korea, which was visited within the scope of the mobility, were shared. At the same time, South Korean traditions/customs were mentioned.
Keywords: University libraries; librarians; professional development; ERASMUS Personnel Exchange Program; Myongji University Library